Artificial Intelligence and Human Resource Competencies in SMEs: A Bibliometric Review of Research Trends - Suginam Suginam; Sopi Pentana; Hafriz Rifki Hafas; Rizky Indra Saputra; Rizkah Fadillah (Graha Mitra Edukasi, 2026)
This study aims to analyze the development of research trends regarding artificial intelligence and human resource competence in small and medium enterprises (SMEs) through a bibliometric approach. The research background is based on the increasing role of artificial intelligence in the digital transformation of organizations, especially SMEs, which requires the readiness of human resource competencies as the main supporting factor in its implementation. The research method uses a bibliometric approach by analyzing scientific articles published in the period 2021–2026 from reputable databases such as Scopus, Web of Science, Google Scholar, Dimensions, and SINTA. Data were analyzed using VOSviewer and Publish or Perish software to map publication trends, keyword relationships, author collaboration patterns, and the impact of scientific citations. The results show that the number of publications related to this theme has increased significantly in the last five years, with the dominant keywords including artificial intelligence, human resource competence, SMEs, and digital transformation. In addition, the results of the analysis show a shift in research focus from a technology-based approach to an integrative approach that places human resource competencies as a strategic factor in the success of artificial intelligence adoption. This study concludes that the integration between artificial intelligence and human resource competencies is an important foundation in improving the competitiveness and sustainability of SMEs in the digital era.